The Effect of Hyperthyroidism on Leptin and Immunoglobuline E Levels in Asthma Patients - Hallab, Noor; Mnaf, Fariel; Hashm, Hashm (Iraqi Journal of Science, 2023)
This study aimed to explain the relationship between hyperthyroidism and asthma by indicating the effect of thyroid hormones (T3 and T4) on leptin and IgE levels.To determine whether T3 and T4 alters serum leptin and IgE levels, twenty newly diagnosis hyperthyroidism patients,twenty asthma patients, ten asthma with hyperthyroidism patients and ten (healthy) as a control were studied. Serum samples were collected to measure the leptin and IgE levels in addition to T3,T4 and TSH Levels. The results revealed a significant (p<0.05) increase in leptin and IgE levels in hyperthyroidism, asthma and hyperthyroidism with asthma patients compared with the control group.These results indicated that elevation in T3 and T4 induced asthma,by affected these hormones on differenation of adipocyte tissue that cause increase of leptin hormone and increase O2 consumes from cells and make immune cell in activated state results increase IgE level.This study concluded there is a relationship between hyperthyroidism and asthma through increase Leptin and IgE.